Service Quality, Promotion, and Brand Trust on ShopeeFood Customer Loyalty in Badung Regency - I Putu Arya Sukayadnya; Made Mulia Handayani; Cokorda Istri Agung Vera Nindia Putri (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: Research seeks to analyze how Service Quality, Promotional efforts, and Brand Trust influence consumer retention toward ShopeeFood delivery services in Badung Regency. Methodology/approach: Study took place in Badung Regency using a survey involving 150 randomly chosen participants. Information was obtained via questionnaires that included respondent profiles and the studied factors. The gathered information was processed through statistical techniques software assess validity, reliability, as well as both joint and individual influences of these factors on consumer loyalty. Results/findings: The results show that overall, Service Quality, Promotional activities, and trust in the brand exert a significant and favorable influence on user retention when utilizing ShopeeFood services in Badung Regency. Each factor likewise demonstrates an individual positive impact on consumer commitment, emphasizing their role in strengthening loyalty. Conclutions: Service Quality, Promotion, and Brand Trust are key factors that service providers, like ShopeeFood, should focus on to increase customer loyalty in Badung Regency. Limitations: Scope regarding this study involves confined toward Badung Regency and relies on quantitative survey responses, making the results less applicable to different areas. Contribution: This research provides valuable insights for food delivery service providers and academics in the management field, particularly in understanding the critical factors influencing customer loyalty. The results serve as a basis for developing marketing strategies and improving Service Quality within the food delivery industry in Indonesia.